Acoustic Feedback in Gait Rehabilitation—Pre-Post Effects in Patients With Unilateral Hip Arthroplasty - Reh, Julia; Schmitz, Gerd; Hwang, Tong-Hun; Effenberg, Alfred O. (Frontiers in Sports and Active Living, 2021)
It is known that patients after unilateral hip arthroplasty still suffer from a deficient gait pattern compared to healthy individuals one year after surgery. Through the method of gait sonification, it may be possible to achieve a more efficient training and a more physiological gait pattern. Increased loads on the musculoskeletal system could thus be reduced and rehabilitation times shortened. In a previous investigation with this patient group, we found immediate gait pattern changes during training with dual mode acoustic feedback (real-time feedback [RTF] and instructive model sequences [IMS]). To determine whether an effect persists without the immediate use of acoustic feedback, we analyze data from four times of testing. Following unilateral hip arthroplasty 22 patients participated in an intervention of ten gait training sessions of 20 minutes each. During gait training the sonification group (SG) (n = 11) received an acoustic feedback consisting of RTF and IMS compared to a control group (CG) (n = 11). Pre-test, intermediate test, post-test, and re-test were conducted using an inertial sensor-based motion analysis system. We found significant effects (α = 0.05) regarding step length and range of motion (RoM) of the hip joint. Step length of the affected leg increased in the SG from intermediate test to posttest but decreased in the CG (intermediate test: [SG] 0.63 m ± 0.12 m, [CG] 0.63 m ± 0.09 m; post-test: [SG] 0.66 m ± 0.11 m, [CG] 0.60 m ± 0.09 m). However, from the post-test to the re-test a reverse development was observed (re-test: [SG] 0.63 m ± 0.10 m, [CG] 0.65 m ± 0.09 m). Also, from post-test to re-test a decrease in the RoM of the unaffected hip for the SG but an increase for the CG could be observed (post-test: [SG] 44.10° ± 7.86°, [CG] 37.05° ± 7.21°; re-test: [SG] 41.73° ± 7.38°, [CG] 40.85° ± 9.28°). Regarding further parameters, significant interactions in step duration as well as increases in stride length, gait speed, cadence, and a decrease in ground contact time from pre-test to re-test were observed for both groups.